2018
DOI: 10.1007/s11906-018-0814-x
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamic Ion Channels in Hypertension

Abstract: Hypertension is a prevalent and major health problem, involving a complex integration of different organ systems, including the central nervous system (CNS). The CNS and the hypothalamus in particular are intricately involved in the pathogenesis of hypertension. In fact, evidence supports altered hypothalamic neuronal activity as a major factor contributing to increased sympathetic drive and increased blood pressure. Several mechanisms have been proposed to contribute to hypothalamic-driven sympathetic activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 96 publications
0
5
0
Order By: Relevance
“…Hypothalamus plays a critical role in modulating the neuroendocrine system and thus it is essential for the internal homeostasis of body temperature, blood pressure, water intake, and control over the circadian rhythm ( Cooper, 1966 ; Geraldes et al, 2018 ). Previous single-cell RNA sequencing investigations suggested that principal hypothalamic neuronal types include both glutamatergic and GABAergic neurons and a small number of histaminergic neurons related to modulating circadian rhythm ( Chen et al, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…Hypothalamus plays a critical role in modulating the neuroendocrine system and thus it is essential for the internal homeostasis of body temperature, blood pressure, water intake, and control over the circadian rhythm ( Cooper, 1966 ; Geraldes et al, 2018 ). Previous single-cell RNA sequencing investigations suggested that principal hypothalamic neuronal types include both glutamatergic and GABAergic neurons and a small number of histaminergic neurons related to modulating circadian rhythm ( Chen et al, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…Among the core functional pathways, the first one is the classic ACE-Ang II-AT 1 R axis, whose activation contributes to elevated blood pressure and vascular dysfunction [ 25 ], and the second one is the nonclassical ACE II-Ang-(1-7))-MasR axis, which helps lower blood pressure and inhibit vasoconstriction [ 26 ]. The hypothalamus is considered to be the blood-pressure-regulating center [ 27 , 28 ]. In the present study, the increased expression of ACE and AT 1 R in the hypothalamus of male rats might be partially responsible for the elevated blood pressure in the CEF + HFD group.…”
Section: Discussionmentioning
confidence: 99%
“…The results needed to be further proved by cohort study. Second, due to the lack of relevant information, this study had not adjusted confounding factors including dietary pattern [ 38 ] or intake of sodium [ 39 ] and potassium [ 40 ]. Third, Using BIA as the principle to estimate body fat, the estimation error could not be eliminated and it would vary with the change of body fat level.…”
Section: Discussionmentioning
confidence: 99%